SISTEM KEKERABATAN KEPURUSA DI BALI - Asmarajaya, I Made (Fakultas Hukum Universitas Mahasaraswati Denpasar, 2017)
Indonesian country identic with the diversity religion, race or subrase, and tradition. The relegion followed is embodied in costomary law. In someÂ society as for Bali between relegion and custom canât be seperated such as the customary law in Bali. We canât define between relegion and custom becouse all aspect of life are totally influenced by Hindu religion or the believe. Their believe exercise in some system such as the family system. According antropologic science there are three system of families those are patrilinial, matrilineal and parental. Those system exercised in different cummunities. Patrilineal system exercised the people of Bali who follow the Hindu religion. There is no parental term in Bali. ItÂ means only the man my become the leader of the family and the decendance must follow the line if the father. In heritage law also only the man can herits. For the woman only accept the thing from their parent during the parent still alife. This institution called âjiwa danaâ.There are some reasons Bali people exercise kepurusa system. First, generally the man much more stronger than woman. Second, woman monthly gets menstruation. During this period the woman canât pray and entering temple.